In vitro investigation of erosive effect of carbonated beverages on enamel and dentin - Panić Zorica; Stojšin Ivana; Janković Ognjenka; Vukoje Karolina; Brkanić Tatjana; Tadić-Latinović Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Excessive consumption of acidic dietary substances, such as carbonated beverages, increased the chances of dental erosion. The aim of this study was to determine influence of carbonated beverages on enamel and dentin, during different intervals. Methods. Sixty samples were obtained from fifteen impacted third molars. Tooth crown was divided into four parts. One part was a control sample, immersed in destilled water and other three parts were the experimental samples, stored in the following tested beverages: carbonated water, Coca-Cola and Schweppes Bitter Lemon. For each beverage, pH was measured before immersion of the samples. The first group of twenty samples were analysed and photographed, using a Scanning Electron Microscope (SEM), after 60 minutes, the second group after 24 hours and the third group after 7 days of exposure to drinks. The enamel was analysed on the outer surface of the cusps and longitudinal section. Dentin was analysed on longitudinal section. An individually adopted scale was used for determination of the degree of erosive changes of these dental tissues. The data were analysed using the analysis of varance (ANOVA). Results. The pH levels of the tested beverages was bellow the critical pH for enamel demineralisation. The SEM images showed different intensity of erosive changes caused by the tested beverages. The analysis by ANOVA revealed a significant difference between all groups of the treated samples, after 60 minutes of exposure to beverages. The highest values of erosive changes showed the samples that were immersed in Schweppes Bitter Lemon. The analysis of the samples after 24 hours and 7 days showed that the samples immersed in Coca-Cola and Schweppes Bitter Lemon can be classified as one group that was statistically significantly different compared with the control samples and samples immersed in carbonated water. Conclusion. Prolonged exposure of dental tissue to carbonated beverages cause erosive changes and a loss of surface profile.